2017
DOI: 10.1128/aac.02570-16
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Entinostat Heals Experimental Cholera by Affecting Physical and Chemical Barrier Functions of Intestinal Epithelia

Abstract: We have shown previously that oral treatment with sodium butyrate or phenylbutyrate in an experimental model of shigellosis improves clinical outcomes and induces the expression of the antimicrobial peptide CAP-18 in the large intestinal epithelia. In a subsequent study, we found that entinostat, an aroylated phenylenediamine compound, has similar therapeutic potential against shigellosis. In this study, we aimed to evaluate entinostat as a potential candidate for host-directed therapy against cholera in an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The HDACi class I inhibitor entinostat has been reported to reduce inflammation and bone loss in an experimental murine arthritis model []. Additionally, entinostat proved to be effective in mitigating the phenotypes of bacterial infection models with salmonella and Escherichia coli [] and demonstrated beneficial effects in a rabbit in‐vivo model of cholera infection []. Often studied at single loci, indirect enrichment of histone acetylation and concomitant transcriptional activation is the paradigmatic mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…The HDACi class I inhibitor entinostat has been reported to reduce inflammation and bone loss in an experimental murine arthritis model []. Additionally, entinostat proved to be effective in mitigating the phenotypes of bacterial infection models with salmonella and Escherichia coli [] and demonstrated beneficial effects in a rabbit in‐vivo model of cholera infection []. Often studied at single loci, indirect enrichment of histone acetylation and concomitant transcriptional activation is the paradigmatic mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Entinostat stimulates CAMP gene expression via activation of STAT3 and HIF-1α transcription factors in human colonic epithelial cells 29 . Moreover, oral treatment of Shigella - and Vibrio cholera- infected rabbits with Entinostat improved their survival and restored production of the rabbit cathelicidin CAP-18 in gut epithelial surfaces 30,31 . Entinostat is an HDACi undergoing clinical trials as adjunctive cancer therapy 32 .…”
Section: Introductionmentioning
confidence: 99%
“…While HDPs are being directly explored as novel antimicrobials or vaccine adjuvants against drug-resistant infections (Choi et al, 2012 ; Hilchie et al, 2013 ; Mansour et al, 2014 ), modulating the synthesis of endogenous HDPs has shown promise in the treatment of shigellosis, pulmonary tuberculosis, cholera, and enteropathogenic E. coli -induced diarrhea (Raqib et al, 2012 ; Al-Mamun et al, 2013 ; Mily et al, 2015 ; Sarker et al, 2017 ). In fact, a number of small-molecule compounds such as butyrate, vitamin D 3 , bile acids, and histone deacetylase inhibitors have been shown to induce HDP synthesis in humans without provoking inflammation (Campbell et al, 2012 ; Van Der Does et al, 2012 ; Lyu et al, 2015 ; Yedery and Jerse, 2015 ).…”
Section: Introductionmentioning
confidence: 99%